Ánima Sola - Domínguez Virgen, J. Carlos (2023)
In the article, we take Ánima Sola, a play about femicides in Mexico, as a starting point to problematize how stage creation assumes the ethical responsibility of representing the victims of violence. We review the notion of event, a concept discussed in different disciplines including Theater and Performing Arts. Using oral history as a methodological approach, more specifically in-depth interviews with the actresses involved in the project, we propose the concept of event in a life trajectory as an analytical aspect that complements other definitions, including that of theatrical event (Dubatti, 2017) and that of event as a set of effects that surpass their causes (Žižek, 2014). The conceptual framework is based on Merleau-Ponty's phenomenology (2002) and José Antonio Sánchez's reflections (2016) on ethics and representation, among others, to reveal that Ánima Sola as a dramatic text demands a disposition and involvement from the subjectivity of the actresses, an event that is expressed as an ethical manifestation of representation.